Two-year radiographic and clinical outcomes from the Canadian Methotrexate and Etanercept Outcome study in patients with rheumatoid arthritis - Keystone, Edward C. (Rheumatology (Oxford), 2016)
Objective. To evaluate radiographic and clinical outcomes up to 24 months in patients with RA enrolled in the Canadian Methotrexate and Etanercept Outcome study. Methods. In this open-label non-inferiority trial, patients with inadequate response to MTX received etanercept plus MTX for 6 months and then were randomized to either etanercept monotherapy or continued etanercept plus MTX until 24 months. Radiographic data were analysed using the modified total Sharp score (mTSS), joint space narrowing and erosion scores. Secondary outcomes included the 28-joint DAS with ESR (DAS28-ESR), Simplified Disease Activity Index, Clinical Disease Activity Index, HAQ Disability Index (HAQ-DI) and safety. Results. Two hundred five of 258 patients enrolled were randomized (98 etanercept, 107 etanercept plus MTX). At month 24, the mean increase from baseline to month 24 for the etanercept and etanercept plus MTX arms, respectively, for the mTSS were 0.4 (s.d. 1.9) and 0.0 (s.d. 1.4); for joint space narrowing, 0.1 (s.d. 0.6) and 0.0 (s.d. 0.7) and for erosion, 0.3 (s.d. 1.5) and 0.0 (s.d. 1.0). At month 24, the mean increase from month 6 mean scores/count increases for DAS28-ESR were 0.56 (s.d. 1.26) and 0.08 (s.d. 1.50); for Simplified Disease Activity Index, 4.7 (s.d. 13.1) and 0.9 (s.d. 12.5); for Clinical Disease Activity Index, 4.1 (s.d. 12.3) and 1.0 (s.d. 12.3) and for HAQ-DI, 0.20 (s.d. 0.45) and 0.02 (s.d. 0.54). Patients with DAS28-ESR low disease activity (LDA)/remission at month 6 had numerically better outcomes at month 24 than patients with moderate to high disease activity at month 6. In patients with LDA/remission at month 6, outcomes were similar at month 24 between etanercept monotherapy and etanercept plus MTX, whereas patients with moderate to high disease activity at month 6 had numerically better outcomes with etanercept plus MTX than etanercept at month 24. There were no new safety signals and serious adverse events were not different between groups. Conclusion. These results support the possibility of discontinuing MTX in patients who have tolerability issues with MTX if they achieve LDA/remission. Trial registration: ClinicalTrials.gov (https://clinicaltrials.gov/; NCT00654368).